2012
DOI: 10.1007/s10658-012-0128-9
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic diversity of Phytophthora sojae pathotypes from Brazil

Abstract: Phytophthora root and stem rot has developed in commercial soybean fields since 2006 in Brazil, and cultivars with resistance to this disease have not been targeted for this region. Thus, the Phytophthora sojae pathotypes are expected to have virulence to few if any of the Rps genes. The objectives of this study were to characterize the pathotype diversity of P. sojae in Brazil, determine the distribution of the pathogen and predict which Rps genes will be effective and should be used in breeding programs. Iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 23 publications
2
27
0
2
Order By: Relevance
“…However, because of selection for mutants, recombinants or immigrants, the local pathogen population may become adapted and overcome the resistant cultivar (McDonald & Linde, ). Previous studies have found that most resistance genes currently used against P. sojae have been broken down (Kaitany et al ., ; Cui et al ., ; Costamilan et al ., ). In this study, dramatic changes in virulence frequencies of the pathogen were found over time.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, because of selection for mutants, recombinants or immigrants, the local pathogen population may become adapted and overcome the resistant cultivar (McDonald & Linde, ). Previous studies have found that most resistance genes currently used against P. sojae have been broken down (Kaitany et al ., ; Cui et al ., ; Costamilan et al ., ). In this study, dramatic changes in virulence frequencies of the pathogen were found over time.…”
Section: Discussionmentioning
confidence: 97%
“…However, because of selection for mutants, recombinants or immigrants, the local pathogen population may become adapted and overcome the resistant cultivar (McDonald & Linde, 2002). Previous studies have found that most resistance genes currently used 0 49 5 41 5 79 95 72 95 100 100 95 82 95 39 2013 13HC 5 30 0 75 10 90 80 65 85 100 100 100 80 100 20 2013 13YY 8 27 4 81 8 92 96 73 100 100 96 92 54 92 26 2012 12YY 7 14 0 7 0 93 93 14 64 100 100 93 100 21 14 2012 12BS 18 0 0 0 6 88 65 6 76 100 100 88 71 18 17 Total 6 29 3 46 6 87 88 54 87 100 99 93 76 75 116 against P. sojae have been broken down (Kaitany et al, 2001;Cui et al, 2010;Costamilan et al, 2012). In this study, dramatic changes in virulence frequencies of the pathogen were found over time.…”
Section: Discussionmentioning
confidence: 99%
“…Difference in virulence property as observed in this study has also been reported in other Phytophthora spp. [22,23] and in other plant pathogens [24,25]. No correlation could be elucidated from the phenotypic or genotypic characteristics and geographical origin of the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…El gen Rps 1k, que ha sido universalmente utilizado en programas de mejoramiento debido a su eficacia contra 21 razas fisiológicas (Mc Blain y Schmitthenner, 1991) y sigue siendo altamente efectivo en Brasil (Costamilan et al, 2013), fue quebrado por once aislamientos de diferentes localidades, en el periodo 1998-y en el periodo 2013-2016 fue quebrado por un 84,7 % de los aislamientos del SEBA y por un 63,75 % del NBA respectivamente. Este resultado indica que las poblaciones argentina y brasileña de Ph.…”
Section: Discussionunclassified
“…sojae del mismo origen geográfico, tanto en Argentina (Gally et al, 2007) como en diferentes Estados de EEUU, Ohio (Dorrance et al, 2003 b), Arkansas (Jackson et al, 2004), Illinois (Malvick y Grunden, 2004) y Dakota del Norte (Nelson et al, 2008). Así como se informó en Brasil (Costamilan et al, 2013), el aumento de la complejidad de la virulencia encontrado en este estudio es probablemente el resultado de un largo período de producción continua de cultivares de soja con genes Rps y la gran adopción del sistema de siembra directa en ambos países. La presión de selección ha sido seguramente inducida por cultivares con virulencia creciente a un mayor número de genes Rps, posiblemente potenciado por una población local de tipo salvaje (Drenth et al, 1996).…”
Section: Discussionunclassified